Controlled orientation of molecular-beam-epitaxial BaTiO3 on Si(001) using thickness engineering of BaTiO3 and SrTiO3 buffer layers. (16th May 2017) - Hsu, Min-Hsiang Mark; Van Thourhout, Dries; Pantouvaki, Marianna; Meersschaut, Johan; Conard, Thierry; Richard, Olivier; Bender, Hugo; Favia, Paola; Vila, Maria; Cid, Rosalia; Rubio-Zuazo, Juan; Castro, German R.; et al.
Abstract: Monolithically integrating BaTiO3 on silicon substrates has attracted attention because of the wide spectrum of potential novel applications ranging from electronics to photonics. For optimal device performance, it is important to control the BaTiO3 domain orientation during thin film preparation. Here, we use molecular beam epitaxy to prepare crystalline BaTiO3 on Si(001) substrates using a SrTiO3 buffer layer. A systematic investigation is performed to understand how to control the BaTiO3 domain orientation through the thickness engineering of the SrTiO3 buffer layer and the BaTiO3 layer itself. This provides different possibilities for obtaining a given BaTiO3 orientation as desired for a specific device application.